Determinants of Dyslipidemia in Africa: A Systematic Review and Meta-Analysis - Obsa, Mohammed S.; Ataro, Getu; Awoke, Nefsu; Jemal, Bedru; Tilahun, Tamiru; Ayalew, Nugusu; Woldegeorgis, Beshada Z.; Azeze, Gedion A.; Haji, Yusuf (Frontiers in Cardiovascular Medicine, 2022)
Background Dyslipidemia is a common public health problem in Africa. It has emerged as an important cardiovascular risk factor. It has been steadily increasing due to economic growth, urbanization, and unhealthy dietary pattern. Therefore, it is essential to identify determinants of dyslipidemia to prevent the condition and reduce its long-term sequel. Methods Combinations of search terms with Boolean operators were used to retrieve studies from PubMed, EMBASE, Cochrane Database, Cinahl, Scopus, Mednar, and Google Scholar. The methodological quality of each article was evaluated based on the 2017 Joanna Briggs Institute (JBI) Critical Appraisal checklist for prevalence studies. After evaluation of each study against these criteria, studies with a minimum score of 7 or above out of 9 JBI checklists were included. We included articles presented in the English language. The Cochrane Q test was used to assess the heterogeneity across studies. The visual assessment of publication bias was done by creating a funnel plot. The possible causes of heterogeneity were explored by subgroup analyses. Egger's weighted regression test was used to assess the presence of publication bias. Statistical analyses were done by using the STATA software version 14. Result A total of 24 articles involving 37,902 participants from 10 African countries were included. The overall pooled prevalence of dyslipidemia was 52.8 (95% CI 40.8–64.9). Individuals with a body mass index (BMI) >25.0 kg/m2 and waist circumference (WC) >94 cm were, respectively, 2.36 (95% CI (1.33–4.18), p < 0.001) and 2.33 (95% CI (0.75–0.29) p < 0.001) times more likely to develop dyslipidemia than those with lower values. Furthermore, patients with diabetes mellitus (DM) and hypertension (HTN) were 2.32 (95% CI (0.89–6.05) p < 0.001) and 2.05 (95% CI (1.31–3.21), p < 0.001) times more likely to present with dyslipidemia than non-diabetic patients and those without HTN. Conclusion This study revealed that the prevalence of dyslipidemia is relatively high among study participants in African countries and the independent predictors of dyslipidemia were BMI >25.0 kg/m2, WC > 94 cm, raised blood glucose level, and raised blood pressure. Therefore, there should be a pressing public health measure to prevent, identify, and treat dyslipidemia with the special emphasis on obese, diabetic, and hypertensive patients.